1988
DOI: 10.1002/hep.1840080115
|View full text |Cite
|
Sign up to set email alerts
|

Is the hypotension of cirrhosis a GABA-mediated process?

Abstract: Systolic and diastolic blood pressures were recorded in 176 ambulant patients with chronic liver disease, including 36 patients with compensated cirrhosis (Group I), 119 patients with noncirrhotic chronic liver disease (Group II) and 21 patients with benign structural or functional liver disease (Group III). Group I patients had significantly lower systolic (113.0 +/- 2.2 mm Hg, mean +/- S.E.) and diastolic (65.3 +/- 1.7 mm Hg) pressures than Group II patients (125.8 +/- 3.5 and 76.6 +/- 1.5 mm Hg, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…5,6 This might in principle be supported by the favorable cardiovascular risk profiles of cirrhosis per se in terms of the hemostatic defects such as impaired coagulation, thrombocytopenia, and platelet dysfunction, low blood pressure and cholesterol levels, and high levels of circulating estrogens, as well, seen in previous and, in part, also in the current series. 7,35,38 However, because we did not find these factors to be significantly prognostic, this argument may be fallacious. On the other hand, some recent studies have suggested that cirrhotic conditions promote CAD because moderate to severe coronary stenotic disorders seemed to be relatively prevalent in LT candidates, accounting for up to 27% of the candidates.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…5,6 This might in principle be supported by the favorable cardiovascular risk profiles of cirrhosis per se in terms of the hemostatic defects such as impaired coagulation, thrombocytopenia, and platelet dysfunction, low blood pressure and cholesterol levels, and high levels of circulating estrogens, as well, seen in previous and, in part, also in the current series. 7,35,38 However, because we did not find these factors to be significantly prognostic, this argument may be fallacious. On the other hand, some recent studies have suggested that cirrhotic conditions promote CAD because moderate to severe coronary stenotic disorders seemed to be relatively prevalent in LT candidates, accounting for up to 27% of the candidates.…”
Section: Discussionmentioning
confidence: 74%
“…We found that the prevalence of obstructive CAD among cirrhotic patients without symptoms or histories of heart attack did not differ significantly from that among a propensity score-matched nonhepatic control group. In a multivariable analysis, the prevalence was completely independent of clinical parameters that can be affected by the severity of liver cirrhosis, such as hyperlipidemia, arterial hypertension, diabetes mellitus, and BMI [32][33][34][35][36] although the cirrhotic cases were at higher risk of nonobstructive lesions, which have a more favorable course. 25,[27][28][29][30] The prevalence of obstructive disease in both sets was ≈8%, and the traditional clinical predictors such as age, sex, hypertension, and diabetes mellitus contributed substantially to coronary narrowing in the hepatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Indeed, the physiologic adaptations to chronic liver failure will be markedly altered by the posttransplant circulatory environment. 37,38 Vasopressin is released in response to dehydration, salt administration, hypotension, and surgical stress. [39][40][41][42] Atrial distension, not increased atrial pressure, and acute but not chronic salt loading lead to increased circulating ANF.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest the possible involvement of other humoral vasodilators, but a definitive pathogenic role for any of these substances remains elusive. This list includes: glucagons [37] , prostaglandins [38] , GABA [39] , VIP [40] , bile acids [41] , endotoxin, histamine [42] and adenosine [43] .…”
Section: Endocannabinoidsmentioning
confidence: 99%